Analisis Strategi Penghimpunan Dana Bantuan Sosial Yayasan Damai Aqsha Samarinda Pada Masa Sebelum dan Saat Pandemi - Syahrul Ramadhan; Alfitri Alfitri; Nur Rahmatullah (Borneo Islamic Finance and Economics Journal, 2022)
The condition of the Aqsa Damai Foundation, whose purpose is to contribute to outside Indonesia, is still able to exist despite the Covid-19 pandemic. The study aims to understand the strategy of the Aqha Samarinda Damai Foundation in conessllecting social assistance funds before and during the pandemic, as well as knowing the influencing factors in implementing strategies for collecting social assistance funds during the pandemic.In this study, the research used qualitative research method using descriptive research. This is because the data collected is in the form of words, pictures and not numbers. Data collection techniques using observation, interviews and documentation. And the data analysis techniques used are data reduction, data presentation and conclusion drawing.The results of this study indicate that the strategy for collecting social assistance funds is in the form of Direct fundraising and Indirect fundraising. The Direct Fundraising methods implemented include Daulah Sheikh/Sheikho, Cheerful Fairy Tales, Charity Concerts, Watch Together, Boar Tunas Collection, Commitment Cards, Establishment of Outlets, work partners, and account transfers, while the Indirect Fundraising method is through WhatsApp, Instagram , facebook, tiktok and twitter. Supporting factors for the implementation of the various prepared strategies are Indonesia's attitude of always helping Palestine, achieving feedback from the activities carried out, quality services and appreciation for donors, educated people, professional human resources, quality amil quality, strategic location of institutions and innovation. from the institution. Meanwhile, the inhibiting factors that affect the fundraising strategy are the COVID-19 pandemic, the difficulty of obtaining activity permits and innovations that must always be prepared. Keywords: Strategy, Collection, Social Assistance Fund, Pandemi.